A Model of Indonesian Consumers' Online Shopping Behavior, an Extension of TAM - Wibasuri, Anggalia; Pratisti, Cahyani; Nurjanah, Indah Ike (International Journal of Artificial Intelligence Research, 2023)
The aim of determining the online shopping behavior of Indonesian consumers was to create a model of online shopping behavior in Indonesia. The specific goal was to examine and develop a model of online shopping behavior in Indonesia using the Technology Acceptance Model, which is integrated with e-trust, security, and perceived risk as moderators. This research used a descriptive analysis method with a quantitative approach. Primary data were obtained by distributing questionnaires with 385 respondents as samples, using an online survey. The questionnaire was analyzed to determine the effect of the Technology Acceptance Model on Purchase Intention in online marketing through the moderating role of trust, security, and risk. The object of this research was online shopping users in Indonesia. The population of this study was all consumers who used the Internet to make online purchases (Blibli.com, Tokopedia.com, Bukalapak.com, Beribenka.com, Shopee.com, or other online product marketing sites) either through smartphone media or other media (PCs, and laptops). Samples were taken using the non-probability sampling technique with the purposive sampling method and analyzed using SEM. The results showed that perceived usefulness positively affected consumer attitudes, perceived ease of use positively affected consumer attitudes, perceived ease of use positively affected purchase intentions, perceived ease of use affected purchase intentions strengthened by perceived risk, consumer attitudes positively affected purchase intentions, attitudes affected purchase intentions strengthened by security, and attitudes affected purchase intentions strengthened by e-trust.